Evaluation of Nitrogen, Phosphorus, and Potassium Levels in Rice Straw Compost for Sweet Corn Growth in Gorontalo - La Kilo, Akram; Djafar, Yuliyanti Wahab; Iyabu, Hendri (Universitas Negeri Gorontalo, 2023)
This study aims to determine the NPK nutrient content of a mixture of soil and straw compost. -The determination of nitrogen, phosphorus, and potassium levels was carried out using the Kjeldahl method, UV-Vis, and AAS instrument, respectively.The results of the analysis showed that the levels of NPK in the mixture of soil and straw compost, the levels of N 1.6-3.6%, P 0.39-44%, and Potassium 0.14-0.16%, the results obtained that levels of nitrogen, phosphorus met the minimum standard of SNI 19-7030-2004, the potassium content is only slightly or does not meet the standard of SNI/19/7030/2004. The results of the analysis of variance (ANOVA) showed that a mixture of soil and straw compost was suitable as a planting medium for sweet corn which had a significant effect on plant height, stem diameter, stem circumference, and number of leaves.